AsaGEI2d: a new variant of a genomic island identified in a group of Aeromonas salmonicida subsp. salmonicida isolated from France, which bears the pAsa7 plasmid. Issue 4 (19th February 2021) - Vincent, Antony T; Intertaglia, Laurent; Loyer, Victor; Paquet, Valérie E; Adouane, Émilie; Martin, Patrick; Bérard, Céline; Lami, Raphaël; Charette, Steve J
ABSTRACT: Genomic islands ( Aeromonas salmonicida genomic islands, AsaGEI s) are found worldwide in many isolates of Aeromonas salmonicida subsp. salmonicida, a fish pathogen. To date, five variants of AsaGEI ( 1a, 1b, 2a, 2b and 2c ) have been described. Here, we investigate a sixth AsaGEI, which was identified in France between 2016 and 2019 in 20 A. salmonicida subsp. salmonicida isolates recovered from sick salmon all at the same location. This new AsaGEI shares the same insertion site in the chromosome as the other AsaGEI2 s as they all have a homologous integrase gene. This new AsaGEI was thus named AsaGEI2d, and has five unique genes compared to the other AsaGEI s. The isolates carrying AsaGEI2d also bear the plasmid pAsa7, which was initially found in an isolate from Switzerland. This plasmid provides resistance to chloramphenicol thanks to a cat gene. This study reveals more about the diversity of the AsaGEI s. Abstract : AsaGEI2d is the sixth genomic island discovered in the bacterium Aeromonas salmonicida subspecies salmonicida further demonstrating the genomic diversity of this bacterium.